Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 7 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Werauhia leucophylla (L.B.Sm.) J.R.Grant" ] } The dataset includes 7 records from 2 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000180-150527152214153/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences